MASJID SEBAGAI INSPIRASI PRAKTIK MODERASI BERAGAMA - Khasan Ubaidillah; Halim, Abd. (Academic Journal of Islamic Principles and Philosophy, 2024)
Mosques are often used by terrorist groups to develop radical Islamic teachings and doctrines. As a gathering place for Muslims who have diverse backgrounds, the mosque should be a unifier of the people, not a divider of Muslims. This article discusses the experience of religious moderation practices in Solo with a focus on handling young people in campus mosques. By using the approach of involving campus stake holders and collaborating with campus mosque activists among young people, this study has conclusions and recommendations. namely, the mosque as the centre of community religious activities is a strategic land to become the basis for religious moderation activities, so that mosque managers / mosque takmir must promote religious moderation values such as tolerance and mutual respect between religious communities starting from the discussion of themes that are carried out to the selection of preachers in their respective mosques. In addition, the experience of interaction with the mosque by each takmir board needs to be documented or recorded as an inspiration for other mosques throughout Indonesia